Assessing visual attention using soccer game videos in elite female soccer players - Su, Q.; Pang, B.; Li, J.; Wu, Y.; Wang, B.; Qin, S.; Zhu, L. (International Journal of Sport Psychology, 2024)
Background Visual attention is critical in team sports, and multiple object tracking (MOT) task is a well-established experimental method for assessing it. This study aims to use a visual tracking task based on a soccer game video to compare the impact of different numbers of targets on the visual tracking performance of soccer players and that of non-soccer players.